Tectonics of the Asela‐Langano Margin, Main Ethiopian Rift (East Africa). Issue 8 (8th August 2020) - Corti, Giacomo; Sani, Federico; Florio, Alessio A.; Greenfield, Tim; Keir, Derek; Erbello, Asfaw; Muluneh, Ameha A.; Ayele, Atalay
Abstract: We provide insights into the tectonics of the Asela‐Langano margin, at the eastern boundary of the central Main Ethiopian Rift, East Africa, by combining field structural data, remote sensing, analysis of the distribution of faults, new dating of faulted material, and analysis of seismicity. The area is characterized by the occurrence of two fault sets: boundary and axial (Wonji) faults, oriented NE‐SW and NNE‐SSW, respectively. Boundary faults show a complex arrangement in the lake Langano area where they display a rhomboidal pattern, due to the presence of NW‐SE‐trending structures, likely related to preexisting transverse fabrics (the so‐called Langano Rhomboidal Fault System). Overall, our analysis supports a structure of the margin characterized by a monocline affected by a series of minor horsts and grabens; this confirms a marked asymmetry of the central Main Ethiopian Rift, with a master fault system on the opposite, western margin. Cumulative paleostress analysis indicates an overall N115°E extension across the Asela‐Langano margin; however, a local variation of the extension direction from axial (Wonji) faults (∼N90°E) to the boundary faults (∼N115°E) can be observed, pointing to a stress reorientation at rift margins. New 14 C dating of faulted material and seismicity analysis indicate Late Pleistocene–Holocene and current activity on several normal faults affecting the margin. This suggests that extensional deformation in the central Main Ethiopian Rift is accommodated at the rift margins, with subordinate activity on axial faults, supporting that this rift sector reflects an intermediate stage of rift evolution. Plain Language Summary: The motion of tectonic plates away from each other (extension) in rift valleys, such as in East Africa, causes earthquakes, fissuring and faulting of Earth, and volcanic activity. As a rift valley grows, the regions of most intense earthquake and volcanic activity typically changes through time. In this contribution, we combine several different approaches (analysis of satellite images and surface topography, field observations of geology and faults, and analysis of recent earthquakes) to understand the tectonics of the East African rift in Ethiopia. We identify which faults are most active using the geology and location of earthquakes and also measure the direction in which the faults move. Recent earthquakes include a magnitude 5.3 earthquake in January 2017. We also show that the youngest and currently active faults are associated with volcanoes in the rift valley. Overall, our results improve the knowledge of the deformation, seismicity, and volcanism of the rift valley in Ethiopia, which can help scientists understand how a rift valley develops and which regions are currently hazardous. Key Points: We provide new insights into the architecture and the recent and active tectonics of the Asela‐Langano margin, central Main Ethiopian Rift Architecture of the margin characterized by a monocline affected by a series of minor horsts and grabens confirms a marked rift asymmetry Late Pleistocene–Holocene and current activity on several normal faults affects the margin, where stress reorientation is observed